The Effect of Mass Communication and Social Media on Teenagers - Hayati; Geofakta Razali (PT FORMOSA CENDEKIA GLOBAL, 2023)
The media is something that cannot be separated from humans in society, as well as the process of communication, especially mass communication, this is one side of the coin that we cannot sort and choose when we want to discuss it. Mass Communication and Media can change a culture or habit that already exists in society or can even create a new culture. The influence that will appear on society could have a positive impact or even a negative impact. Society is formed by several people or individuals, groups, organizations which then become a heterogeneous society. In this paper the author tries to describe the influence that mass communication and the media have on society and culture, through direct observations and observations made in the community